Production Of Laccase By A Locally Isolated Fungus For Biodegradation Of Selected Agrowastes - Ang, Kong Nian (2007)
The present study was conducted to screen the significant laccase (ligninolytic enzyme) producers from locally isolated white-rot fungi using agitated and non-agitated culture conditions. The highest laccase producer, identified as Pycnoporus sp. (strain S16) was selected for the optimisation of laccase production with particular attention to the effect of physiological factors on laccase production using submerged culture technique. Laccase was characterised to assist in formulating the best condition for the bioconversion of agro-wastes. Significant laccase production was obtained under carbon-depleted condition and dependent on culture morphology. The culture with high laccase activity was observed with the presence of small mycelial pellets with 1−2 mm diameter. The pellet formation and optimum laccase production influenced by various physiological factors are investigated. The best culture condition obtained consisted of 5 g/L of glucose, 12 mM of nitrogen, inoculum concentration of 8 × 106 spores/mL, initial pH 5, incubation temperature of 37°C and agitation speed of 100 rpm. Under the above culture conditions, the time of fermentation was shortened from 16 days to 7 days with maximum laccase activity of 225 U/L. The characterisation study of concentrated laccase revealed the importance of an acidic condition for the highest laccase activity. The biodegradation study showed that some locally available agro-waste materials are suitable for soluble sugar production and that rice bran gave the best results with 1.90 g/L of soluble sugar produced